What Is Resilience and How Can It Be Nurtured? A Systematic Review of Empirical Literature on Organizational Resilience - Edwine Barasa; Rahab Mbau; Lucy Gilson (Kerman University of Medical Sciences, 2018)
Background Recent health system shocks such as the Ebola outbreak of 2014-2016 and the global financial crisis of 2008 have generated global health interest in the concept of resilience. The concept is however not new, and has been applied to other sectors for a longer period of time. We conducted a review of empirical literature from both the health and other sectors to synthesize evidence on organizational resilience. Methods We systematically searched for literature in PubMed, Econlit, EBSCOHOST databases, google, and Google Scholar and manually searched the reference lists of selected papers. We identified 34 papers that met our inclusion criteria. We analysed data from the selected papers by thematic review. Results Resilience was generally taken to mean a system's ability to continue to meet its objectives in the face of challenges. The concepts of resilience that were used in the selected papers emphasized not just a system's capacity to withstand shocks, but also to adapt and transform. The resilience of organizations was influenced by the following factors: Material resources, preparedness and planning, information management, collateral pathways and redundancy, governance processes, leadership practices, organizational culture, human capital, social networks and collaboration. Conclusions A common theme across the selected papers is the recognition of resilience as an emergent property of complex adaptive systems. Resilience is both a function of planning for and preparing for future crisis (planned resilience), and adapting to chronic stresses and acute shocks (adaptive resilience). Beyond resilience to acute shocks, the resilience of health systems to routine and chronic stress (everyday resilience) is also key. Health system software is as, if not more important, as its hardware in nurturing health system resilience